Interrelationship Between Childhood Obesity and Pediatric Dentistry: A Literature Review - Gülçin Doğusal; Işıl Sönmez (Journal of Pediatric Research, 2017)
Childhood obesity is an important public health problem worldwide with an increasing incidence and prevalance. This increase in the obesity rates can lead to many other health problems. Obesity shows early symptoms in childhood like other chronic diseases such as dental caries and gingivitis, and it will be an important step to prevent their adverse effects at early ages in terms of improving the general wellbeing of the societies. The aim of this review is to point out childhood obesity and its potential risks, and put forward its consequences in terms of oral health as well as offering solutions.